Amharic Folkloric Oral Traditions: Collections for Insiders and for Outsiders - Unseth, Peter; Ze'amanuel, Bitania (Aethiopica, 2022)
The two books of Amharic proverbs and the book of Amharic riddles under review document Amharic oral traditions far beyond what others have done previously. They all build on previous scholarship. In addition, each one adds new examples to what has been published before. But it is also important to note that each book has added significant new methodological contributions to their field. They will be valued by those who use and enjoy Amharic oral traditions in their lives. They will also be valued by scholars who study these Amharic oral traditions. In addition, these books can serve as inspirations and models for speakers of other languages, in the Horn and beyond.